Dose-Response of Intrathecal Morphine When Administered With Intravenous Ketorolac for Post-Cesarean Analgesia: A Two-Center, Prospective, Randomized, Blinded Trial. Issue 2 (April 2017) - Berger, J. S.; Gonzalez, A.; Hopkins, A.; Alshaeri, T.; Jeon, D.; Wang, S.; Amdur, R. L.; Smiley, R.
Abstract : (Abstracted from Int J Obstet Anesth, 28:3–11; 2016) Post–cesarean delivery pain management is very important as the women undergoing cesarean delivery need to recover quickly to take care of the newborns. Spinally administered morphine is recommended by the American Society of Anesthesiology to reduce postoperative pain; however, the optimal dose of morphine that should be used for maximizing analgesic effects is not clear.